Updated Guidance Note on the Fund's Transparency Policy. (Policy Papers; Policy Paper ;, 2014)
This note provides guidance to staff on the implementation of the Fund's Transparency Policy. The objectives of the policy include strengthening the Fund's effectiveness by providing the public with access to Fund views and deliberations, thus informing public debate and building traction for the Fund's advice, supporting the quality of surveillance and of programs, by subjecting the Fund to outside scrutiny, and enhancing the Fund's legitimacy by making the institution more accountable. A Transparency Policy Decision (referred to in the remainder of this note as 'the Decision') sets out rules for the modification and publication of all Board documents.